Relation of Vitamin B12 Levels to Bone Mineral Density of Postmenopausal Women - Original Investigation - Nur Kesiktaş; Nurten Eskiyurt; Ayşe Karan; Semih Akı; Halim İşsever (Galenos Yayinevi, 2009)
Aim: Although vitamin B12 (vit-B12) is known to influence the hemopoeitic and nervous systems, little is known about the skeletal effects of vit-B12. Researchs that demonstrated an association between serum vitamin B-12 concentration and osteoblastic function and its' role in DNA synthesis, which suggesting a relationship between osteoporosis, this randomized controlled trial were planned. Material and Methods: Vit-B12 levels of 740 patients aged between 50-65 years, who were applied to our outpatient clinic because of chronic low back pain were examined and divided with vitamin B-12 levels over or below 400 pg/ml. 26 participant who met all inclusion criteria with vit-B12 level below 400pg/ml were assigned to case group. Among the patients that vit-B12 levels were over 400pg/ml, 20 participants were randomly selected to control group. Bone mineral density (BMD), biochemical measurements, causes of osteoporosis and vit-B12 defiencies were investigated. A computer program was used for statistic evaluation. Results: There was not statistically significant difference between BMD's of case and control groups (p>0.05). When the vit-B12 levels were grouped with over 400 pg/ml, below 200 pg/ml and between 200-400 pg/ml, osteodensimetric examinations of femur neck BMD (p<0.05) were achieved statistically significant difference. Conclusion: The results of this trial highlight an association of vitamin B-12 status with osteoporosis. Vit-B12 defiency is an easy and cheap treatable condition so that reason we suggest that levels of vit-B12 should be investigated. (From the World of Osteoporosis 2009;15:1-6)